Implementasi Pendekatan PDIA dalam Penguatan Motivasi Intrinsik untuk Meningkatkan Kesiapan Kerja Siswa SMK - Ihfi Dzuhriyanul Musthofa; Warju Warju; Grummy Wailanduw; Luthfiyah Nurlaela; Rommy Mochamad Ramdhani (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Graduates of Vocational High Schools (SMK) need to be well-prepared for employment; however, encouraging the internal drive necessary for this preparation continues to be a challenge. This research employed the Problem Driven Iterative Adaptation (PDIA) method to boost intrinsic motivation and improve students' preparedness for the workforce. The study was conducted at SMK Negeri 1 Mejayan, Indonesia, using a quasi-experimental design with non-equivalent control groups involving 66 automotive electrical engineering students. Data were collected through validated questionnaires measuring intrinsic motivation (based on Self-Determination Theory) and work readiness (adapted from established scales), supplemented by classroom observations. Statistical analysis using descriptive methods and the Mann-Whitney U test revealed a significant increase in both intrinsic motivation and work readiness among the experimental group compared to the control group. The PDIA approach, through its iterative cycles of authentic problem identification, collaborative diagnosis, solution testing, and reflective action, successfully established a meaningful learning environment that fostered student autonomy, competence, and social relatedness. This involvement in real problem-solving and flexible learning not only enhanced technical abilities but also fostered important soft skills that are vital for success in the workplace. The results indicate that PDIA is a successful and creative teaching approach that connects vocational education with industry needs by strengthening students' intrinsic motivation, thereby enhancing their overall job market readiness.".